PERANAN PEREMPUAN BALI MENGHADAPI NICA DI BALI 1945 – 1950 - Pidada Ida Bagus Astika; Mileh I Nengah (Universitas Warmadewa, 2021)
Cornellis de Houtman, a group of Dutch sailors landed for the first time in Bali at the end of February 1597. The next Dutch visit was in June 1601 under the leadership of Admiral Cornellis Heemskerck. This second Dutch visit brought a letter from Prince Maurits Van Nasau to Dalem Bekung at the Gelgel palace asking for permission to conduct trade, which was approved by the king. In the 19th century the atmosphere changed in Bali, the Dutch wanted to control this area, so there was resistance by the kings in Bali. This resistance started from the Buleleng War, the Jagaraga War, which continued with the Kusamba War, the Banjar War and Puputan Badung and Puputan Klungkung. This resistance did not end just like that but continued. The arrival of the NICA (Dutch) troops to the island of Bali with their Red Elephant troops, the atmosphere became unsafe. Every area visited by the Red Elephant troops received resistance. The fighters in Bali at this time worked hand in hand to face the NICA (Dutch) troops. In this case, it is not only the elderly, children, old, young, as well as men and women who are struggling. In difficult positions, the role of women is very effective in appearing in front. Women during the struggle against NICA (Netherlands) were not too suspicious. During the face of NICA, women's duties were not only in the cities but also in the forests. As for the duties of women at this time, such as: in the fields of health, communication, religion, logistics, investigation, information, weapons and equipment. Thus the role of Balinese women in the struggle in Bali against the NICA (Netherlands) quite a lot in carrying out their duties in achieving independence. Keywords: Role of Women, Bali, NICA